Differences in Islamic Culture History Learning Outcomes Between Active Learning Strategies Team Quiz Type and Practice Private Madrasah Aliyah Students - Zein, Achyar; Budianti, Yusnaili; Gea, Laely Fitriansyah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Researchers have observed low student learning outcomes in the field of Islamic Cultural History, which cannot be separated from the influence of various factors in learning activities. One of the factors influencing learning outcomes is the teacher's teaching method, which is less appealing, causing students to become bored and pay less attention to the teacher's lessons. A quasi-experimental design model with a 1-way analysis of variance (Anava) and a 2 x 1 design is used in this study. Then, using population and samples, the team quiz strategy and practice rehearsal pairs strategy will be compared as independent variables and student learning outcomes as the dependent variable. There were significant differences in the learning outcomes of Islamic Cultural History when taught using a team quiz active learning strategy versus a practice rehearsal pairs active learning strategy. This is demonstrated by the statistical calculation of the t-test, which yields the value of tcount = 3.00 and the price of ttable = 2.0231. The average learning outcomes of Islamic Cultural History taught with the team quiz strategy = 17.85 were higher than the average learning outcomes of Islamic Cultural History taught with the practice rehearsal pairs strategy = 16.35.